Tutela impuberum v historični perspektivi s poudarkom na statutih srednjeveških primorskih mest na Slovenskem - Kambič, Marko (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2012)
The introduction of the paper provides a description of the modern institute of the protection of the interests of minors without parental care (i.e. the guardianship of minors) and addresses problems related to the naming of such from a historical perspective. Furthermore, it presents the foundations of Roman law with regard to the guardianship of persons under the age of puberty (i.e. tutela impuberum) which, together with medieval legal science, marked the development of this institute in Europe. The central part of the paper comprises an analysis of the provisions on guardianship in the medieval statutes of the nowadays Slovenian coastal towns of Piran, Izola and Koper. On such a basis, the author demonstrates that the aforementioned rules are, despite differences among them and their local particularities, basically a result of the early reception of Roman law.
Keywords: child; otroci; mladoletniki; skrbništvo; socialno skrbstvo; srednji vek; Middle Ages; rimsko pravo; Slovenia; Slovenija